Enhancing tunnel cold resistance in cold regions with overlapping-tiles cold-proof wall - Ke Yin; Rui Wang; Licai Zhao; Hafiz Muhammad Irfan; Xingtong Wang; Yinlei Wang (Case Studies in Thermal Engineering, 2025)
Tunnels in cold regions are susceptible to freeze damage. The overlapping-tiles cold-proof walls (OTCW) proposed in this study can effectively block cold airflow into the tunnel and mitigate freeze damage. The anti-freezing ability of OTCW was validated through model tests and numerical simulations, and the structural design was recommended based on the prevailing wind direction. The results indicate that OTCW effectively blocks cold airflow, with its blocking capacity increasing as the number of wallboards increases. When the angle between the wind direction and the tunnel's transverse is 30°, 45°, or 60°, the average wind speed at the tunnel entrance without a portal structure is 1.8, 2.8, and 3.3 m/s, respectively. OTCW with 1, 3, and 4 layers of wallboards completely blocks the cold airflow. When the wind direction angle is 75°, the wind speed without a portal structure is 3.6 m/s. OTCW with 7 layers of wallboards reduces the wind speed by 72.2 %. Under cold region meteorological conditions, significant low-temperature zones appear in the surrounding rock when no portal structure or open cut tunnel (OCT) is installed. When OTCW is set, most of the low-temperature zones disappear. The anti-freezing effect of OTCW is significant.